3D Game Design Aided by Multi-Dimensional Collision Detection Algorithm with GPU Optimization - Wang, Zikai; Pan, Dasheng; Di, Bo (2023 Third International Conference on Artificial Intelligence and Smart Energy (ICAIS), 2023)
This paper addresses the problem of the 3D game design aided by multi-dimensional collision detection algorithm with GPU optimization. For the designed model, our task will be focused on the 3D game design, the GPU performance on the image computing and neural network computing will be essential, hence, the graph neural network algorithm is considered. This study firstly considers the GPU optimization with shared memory model. Shared memory can be used to design the memory access mode in order to realize the combination of the memory access which improves the efficiency. Then, this study considers the multi-dimensional collision detection algorithm design. In order to achieve the unique representation of matrix translation and also spatial points, this paper then adopts the homogeneous coordinate system in matrix transformation. That improves the traditional model. Furthermore, the 3D game design steps are clarified. Based on the experiment under different scenarios, the game design sample code, the GPU performance and algorithm performance are all tested.